IMPLEMENTASI PROFIL PELAJAR PANCASILA MELALUI PROGRAM GERAKAN TATANEN DI BALE ATIKAN (TdBA) DI KABUPATEN PURWAKARTA - Ela Hayati; Afridha Laily Alindra; Abdah Birrul Walidain; Adya Pramudya Dwi Permata Radianty; Faza Zakiyyan; Devita Fitriyani; Fitri Rohmatul Aulia; Nina Marlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was based on the Merdeka Curriculum which established the Pancasila Student Profile to support the quality of education in Indonesia on the cultivation of students' character in line with the Education movement program in Purwakarta Regency, namely the Tatanen Movement Program in Bale Atikan (TdBA). This research aims to study, analyze the implementation of the Pancasila Student Profile through the Tatanen movement program in Bale Atikan (TdBA) and the effectiveness of the Tatanen movement program in Bale Atikan (TdBA) as a medium for implementing the values of Pancasila Student Profile in Purwakarta Regency. This study used a descriptive qualitative approach method. Data collection techniques used are observation, interview, and documentation. The results of research on the implementation of the Pancasila Student Profile of the Tatanen Movement Program in Bale Atikan start from planning, organization, implementation, supervision, supervision and evaluation. At SDN 1 Sindangkasih has done well in implementing the program with the guidance provided by the Purwakarta Regency Education Office, This project certainly supports the implementation of the Strengthening of Pancasila Student Project because it has similar concepts and shows that the TdBA program is able to integrate local wisdom-based agricultural activities into the school curriculum, instilling character values such as mutual cooperation, independence, responsibility, and support. and environmental concerns. The implementation of the Pancasila Student Profile (P5) reinforcement project through TdBA resulted in various product innovations such as compost fertilizer and ecobrick chairs that support students' creativity development and ecological awareness. However, the implementation of the program was still experiencing several obstacles, so researchers recommended the need for adjustment of time management, technical solutions for schools with land constraints, and the implementation of the program. and build awareness from students so that the TdBA program can be sustainable and increasingly effective in shaping students' character in accordance with the Pancasila Student Profile.